Human resource management department in the context of information society - Česynienė, Rima; Stankevičienė, Asta; Jurgaitytė, Neringa (Information & Media, 2015)
The relationship between a human resource management department and information society has become an integral part in the process of creating the knowledge economy. In order to adapt to global economic changes, accelerating globalization and challenges related with the transformation of societies, the new requirements / demands for a human resource management department are raised. In the era of information society, the new – Y – generation is entering the labour market and human resource management departments as well. This requires fundamental changes to adapt to the new challenges of information society, including the characteristics and expectations of the Y generation. In order to find out how human resource management departments of Lithuanian companies are corresponding to the challenges of information society, a quantitative analysis based on the questionnaire method was conducted. The research included 160 respondents (human resource managers and professionals) from 92 Lithuanian business firms. Based on the empirical results, it was indicated that the human resource management departments of Lithuanian companies still have not faced a strong need for a change, but the near future will require a fundamental revision of the role and functions of human resource management departments.
Keywords: ...